Strategic Choice and Performance Empirical Evidence from Mission Hospitals in Kiambu County Kenya - Mary Wangui Njuguna; Stephen Muathe (European Scientific Journal, ESJ, 2020)
The modern business environment is highly dynamic and the management of every firm is compelled to make effective decisions for the company to remain relevant. Strategic choice is a critical element in the process of formulating a strategy. As a result of the threats that organizations are exposed to, organizations are adopting strategic choices to enhance performance. Despite the challenges that mission hospitals in Kiambu County encounter in the health industry, they are still luring away clients from public hospitals. Therefore, this study’s main objective was to establish the influence of strategic choice on performance of mission hospitals in Kiambu County. Specifically, the study embarked on four objectives; to establish the influence of organizational structure on the performance of mission hospitals in Kiambu County; to determine the influence of technology on performance of mission hospitals in Kiambu County; to determine the influence of leadership on the performance of mission hospitals in Kiambu County; and to establish the effect of resource acquisition on performance of mission hospitals in Kiambu County. The theories that guided this study were the agency theory, open systems theory, contingency theory, and the resource based theory. This study adopted a descriptive design. The study targeted the big four mission hospitals Africa Inland Church Kijabe Mission Hospital; Africa Inland Church cure International Hospital; Presbyterian Church of East Africa. Kikuyu Hospital; and Nazareth Hospital) in Kiambu County. The target population was 80 senior, middle, and operational managers and a census was employed. A semistructured questionnaire was utilized for data collection. Regression results revealed that organizational structure, technology, leadership and resource acquisition were highly significant on the performance of mission hospitals in Kiambu County in Kenya. The study recommended that mission hospitals in Kiambu County should create organizational structures which are in line with the goals being pursued by the mission hospitals. On technology the study recommended for effective management and use of technology infrastructure planning, on leadership, the researcher recommends that leadership development be cascaded to all level of employees/management. This is to help the mission hospitals achieve its objectives on service delivery. On resource acquisition the study recommends that managers should look for ways of motivating human resource in the organization for better performance. Mission hospitals should encourage more training and development of employees to enhance knowledge and skills if they want to sustain performance.